2010
DOI: 10.1016/j.jacc.2009.12.044
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Randomized, Double-Blind, Multicenter, Based on Standard Therapy, Placebo-Controlled Study of the Efficacy and Safety of Recombinant Human Neuregulin-1 in Patients With Chronic Heart Failure

Abstract: rhNRG-1 improved the cardiac function of CHF patients by increasing the LVEF% and showed the capability of antiremodeling by decreasing ESV and EDV compared with pre-treatment. (A Randomized, Double-Blind, Multi-Center, Placebo Parallel controlled, Standard Therapy Based Phase II Clinical Trial to Evaluate the Efficacy and Safety of Recombinant Human Neuregulin-1 for Injection in Patients with Chronic Heart Failure; ChiCTR-TRC-00000414).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
211
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(227 citation statements)
references
References 10 publications
9
211
1
6
Order By: Relevance
“…Therefore, our present results suggest a complex action of NRG1 whereby food intakes and weight gain are both decreased possibly through an increase in leptin, while physical activity and energy expenditure are limited through unknown pathways. However, the possibility of a side-effect induced by NRG1 treatment that might promote a decrease in mouse locomotion cannot be ruled out, although human studies using comparable dose ranges have shown no such significant side-effect induced by chronic NRG1 treatment [15,16]. More studies are now needed to elucidate the origin of the NRG1-induced increase in circulating leptin and the contribution of increased circulating leptin to altered food intakes and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our present results suggest a complex action of NRG1 whereby food intakes and weight gain are both decreased possibly through an increase in leptin, while physical activity and energy expenditure are limited through unknown pathways. However, the possibility of a side-effect induced by NRG1 treatment that might promote a decrease in mouse locomotion cannot be ruled out, although human studies using comparable dose ranges have shown no such significant side-effect induced by chronic NRG1 treatment [15,16]. More studies are now needed to elucidate the origin of the NRG1-induced increase in circulating leptin and the contribution of increased circulating leptin to altered food intakes and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…NRG1 also has a role in cardiac maintenance and indeed clinical trials are underway for its use in heart failure [95]. The potential mechanisms of how NRG1 signaling may modulate nerve repair have not been extensively studied; these will be discussed in more detail later.…”
Section: Treatment With Nrg1 Can Promote Nerve Repairmentioning
confidence: 99%
“…In fact, several studies using animal models of heart failure have demonstrated the therapeutic benefits of neuregulins, which improved cardiac performance, attenuated disease markers, and prolonged animal survival [24,25]. Furthermore, phase I and II clinical trials for chronic heart failure in humans confirmed the favorable effects mediated by neuregulins [26,27], highlighting the therapeutic potential of these growth factors in cardiac repair. In this study, we have examined the efficacy of novel MP-based delivery of NRG1 and FGF1 in a rat model of MI.…”
Section: Introductionmentioning
confidence: 99%